Prognostic value of serum NLR, PLR, P53, K67 level in lymph node metastasis of early gastric cancer: Prognostic value of serum NLR, PLR, P53, K67 level in lymph node metastasis - Wang, Ying (Journal of Medical Biochemistry, 2025)
Abstract Objective: To explore the predictive value of relevant detection indexes and pathological serum NLR, PLR, P53, K67 level in lymph node metastasis (LNM) in patients with early gastric cancer (EGC) after radical surgery. Methods: Clinical data of EGC patients (297 cases, all of whom received radical gastrectomy for gastric cancer) admitted to Sichuan Integrative Medicine Hospital from March 2019 to March 2024 were retrospectively included. The clinical data and pathological results were recorded and compared, and the related predictive factors were analyzed. Results There were 43 cases ( 14.48 % ) of postoperative LNM in 297 EGC patients; The LNM (-) group average number of lymph nodes detected was (28.35±8.23) , which lower than the non-LNM (+) group (33±15), P < 0.01 ; It was found by binary multivariate Logistic regression analysis, the relevant predictors of postoperative LNM in EGC patients were tumor size (OR: 2.582, 95%CI: 1.205-5.534), depth of invasion (OR: 2.953, 95%CI: 1.327-6.573), vascular invasion (OR: 2.724, 95%CI: 1.241-5.976), neuroaggression (OR: 2.681, 95%CI: 1.139-6.311), differentiation type (OR: 2.426, 95%CI: 1.140-5.119) and P53 (OR: 3.133, 95%CI: 1.183 ~ 8.301), P < 0.05; The AUC of ROC curve in the model established based on these indexes is 0.801. Compared with the Non-LNM group (-), the LNM group (+) had a loweroverall survival rate at 1 and 2 years (P < 0.05). Conclusions: Clinically relevant detection indexes and pathological P53 indexes of patients after EGC radical surgery have a good predictive effect on the occurrence of LNM, which can supply help for clinical scientific and reasonable treatment plan.
Keywords: serum NLR, PLR, P53, K67, early gastric cancer; Pathological features; Lymph node metastasis; Risk factors for